EFFECT OF PHOSPHATE ON NODULE PRIMORDIA OF SOYBEAN (Glycine max Merrill) IN ACID SOILS IN RHIZOTRON EXPERIMENTS - Setiyo Hadi Waluyo; Tek An Lie; Leendert ’t Mannetje (Indonesian Agency for Agricultural Research and Development, 2004)
To clarify whether P had a direct or indirect effect on the nodulation process of soybean grown in acid soils from Sitiung, West Sumatra, Indonesia, a series of rhizotron experiments, with special attention given to formation of nodule primordia, was conducted at Laboratory of Microbiology, Wageningen University in 1998-2000. It was shown that Ca and P were essential nutrients for root growth, nodule formation, and growth of soybean in the acid soils (Oxisols). Ca increased root growth, number of nodule primordia, nodules, and growth of the soybean plant. This positive effect of Ca was increased considerably by the application of P. Ca and P have a synergistic effect on biological nitrogen fixation (BNF) of soybean in acid soils. Ca is important for the establishment of nodules, whilst P is essential for the development and function of the formed nodules. P increased number of nodule primordia, thus it also has an important role in the initiation of nodule formation. From this study, it can be concluded that Ca and P are the most limiting nutrients for BNF of soybean in the acid soils of Sitiung, West Sumatra, Indonesia.